Rapid MALDI-MS assays for drug quantification in biological matrices: lessons learned, new developments, and future perspectives - Fresnais, Margaux; Yildirim, Esra; Karabulut, Seda; Jäger, Dirk; Zörnig, Inka; Benzel, Julia; Pajtler, Kristian Wilfried; Pfister, Stefan; Burhenne, Jürgen; Haefeli, Walter E.; Longuespée, Rémi (Molecules, 2021)
Matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) has rarely been used in the field of therapeutic drug monitoring, partly because of the complexity of the ionization processes between the compounds to be quantified and the many MALDI matrices available. The development of a viable MALDI-MS method that meets regulatory guidelines for bioanalytical method validation requires prior knowledge of the suitability of (i) the MALDI matrix with the analyte class and properties for ionization, (ii) the crystallization properties of the MALDI matrix with automation features, and (iii) the MS instrumentation used to achieve sensitive and specific measurements in order to determine low pharmacological drug concentrations in biological matrices. In the present hybrid article/white paper, we review the developments required for the establishment of MALDI-MS assays for the quantification of drugs in tissues and plasma, illustrated with concrete results for the different steps. We summarize the necessary parameters that need to be controlled for the successful development of fully validated MALDI-MS methods according to regulatory authorities, as well as currently unsolved problems and promising ways to address them. Finally, we propose an expert opinion on future perspectives and needs in order to establish MALDI-MS as a universal method for therapeutic drug monitoring.
Gesehen am 04.08.2021